2005
DOI: 10.1158/0008-5472.can-04-4406
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cell–Derived Factor-1α and CXCR4 Expression in Hemangioblastoma and Clear Cell-Renal Cell Carcinoma: von Hippel-Lindau Loss-of-Function Induces Expression of a Ligand and Its Receptor

Abstract: The genetic hallmark of hemangioblastomas and clear cellrenal cell carcinomas (CC-RCCs) is loss-of-function of the von Hippel-Lindau (VHL) tumor suppressor protein. VHL is required for oxygen-dependent degradation of hypoxiainducible factor-1A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
180
2
7

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(199 citation statements)
references
References 45 publications
10
180
2
7
Order By: Relevance
“…39,40 Currently, there are research efforts to utilize this mechanism by local intramyocardial delivery of a protease-resistant CXCL12 to attract progenitor cells to sites of hypoxic damage after myocardial infarction. 41 Moreover, in hypoxic tumors or in tumors that display mutations in the von Hippel-Lindau tumor suppressor protein pVHL (a negative regulator of HIF-1), HIF-1 upregulates CXCR4 expression, 42,43 providing a survival benefit for tumor cells with high CXCR4 expression.…”
Section: Cxcr4: a Unique Chemokine Receptormentioning
confidence: 99%
“…39,40 Currently, there are research efforts to utilize this mechanism by local intramyocardial delivery of a protease-resistant CXCL12 to attract progenitor cells to sites of hypoxic damage after myocardial infarction. 41 Moreover, in hypoxic tumors or in tumors that display mutations in the von Hippel-Lindau tumor suppressor protein pVHL (a negative regulator of HIF-1), HIF-1 upregulates CXCR4 expression, 42,43 providing a survival benefit for tumor cells with high CXCR4 expression.…”
Section: Cxcr4: a Unique Chemokine Receptormentioning
confidence: 99%
“…In particular, cases were considered positive when >10% of the tumor cells showed cytoplasmic and/or membrane expression. These staining and scoring methods have been widely used to evaluate the results of immunohistochemical staining for CXCR4 and CXCL12 (18,19).…”
Section: -Aza-2'-deoxycytidine (5-aza-cdr) Treatmentmentioning
confidence: 99%
“…[27][28][29] Prognostic impact of CXCR4 expression levels on the neoplastic cells has been demonstrated in breast cancer 30 and renal cell cancer. 31,32 Recently, Rombouts and colleagues reported that expression of CXCR4 by CD34 ϩ AML cells is related to Flt3 mutations and unfavorable prognosis. 33 In this study, we examined the prognostic impact of CXCR4 surface expression by the CD34 ϩ and/or CD117 ϩ fraction of AML cells at the time of initial diagnosis in a series of 90 consecutive AML patients.…”
Section: Introductionmentioning
confidence: 99%